IFR-FFR comparison in daily practice: a single-center, prospective, online assessment. Issue 9 (September 2015) - Fede, Alfredo; Zivelonghi, Carlo; Benfari, Giovanni; Pesarini, Gabriele; Pighi, Michele; Ferrara, Angela; Piccoli, Anna; Ariotti, Sara; Ferrero, Valeria; Mura, Daniela Dalla; Battistoni, Monica; Vassanelli, Corrado; et al.
Abstract : Aims: To compare the performance of instantaneous wave-free ratio (iFR) with fractional flow reserve (FFR) in a real-life, prospective, single-center, and independent study. Methods and results: Fifty-four patients were included and 89 angiographic intermediate lesions underwent functional evaluation with both iFR and FFR. FFR was used as the gold standard, and the patients having FFR values 0.80 or less only underwent percutaneous coronary intervention. Linear regression demonstrated close agreement between the two techniques ( R  = 0.83, P  < 0.0001). Receiver operator characteristic analysis confirmed the strong correlation, with an area under the curve approximately equal to unity. iFR detected ischemia with a sensitivity and specificity of 100 and 87%, respectively, thus revealing a positive predictive value of 78% and a negative predictive value of 100%. In addition, according to FFR assessment, percutaneous coronary intervention was performed on 39 lesions (43.8%) in 27 patients (50%), whereas positive iFR values were found in 52 lesions (+14.6% compared with FFR). At clinical follow-up (ranging from 6 to 16 months), all patients remained asymptomatic and none of them experienced major adverse cardiovascular events. Conclusions: In this independent, online, comparison of iFR-FFR values in patients with angiographic intermediate lesions, results are consistent with those derived from previous offline controlled trials, and support the correlation between iFR and FFR in daily clinical practice.